Twenty-Five Years of the Asian Academy of Management Journal (AAMJ): Intellectual Structure Mapping and Bibliometric Review - Imran Ahmed Shahzad; Atallah Fahed Alserhan; Muhammad Farrukh; Nilufar Yasmin; Jason Wai Chow Lee (Asian Academy of Management Journal, 2021)
In commemoration of the 25th anniversary of the Asian Academy of Management Journal (AAMJ), this study presents a general overview on the publication structure of the journal from 1996 to 2019. The study identifies the most productive authors, universities, and countries mainly using the Scopus database. It also enlists the most cited documents of the journal. Besides, the study graphically maps the intellectual structure based on co-citation, bibliographic coupling, and co-occurrence of authors’ keywords. The findings show the prominent Asian profile of the journal where most of the contributions come from the Asian countries and the universities. Specifically, authors from Malaysia and India remain the most frequent contributors. These findings provide readers of AAMJ with an objective overview of the trends of the journal. The study may be useful for future contributors as it provides inputs for the future research agenda.